The influence of Indonesian Sign Language (BISINDO) news broadcasts on the audience’s understanding of information on television - Yusuf, Ahmad Nur Iqbal; Tajibu, Kamaluddin (Jurnal Mercusuar, 2021)
The rapid development of technology today has a significant impact on the flow of information to all levels of society, including people with disabilities, especially the deaf. Deaf people are always identified as unable to hear (deaf) and unable to speak (mute). In Indonesia, there are two legally recognized sign languages, namely Indonesian Sign Language System (SIBI) and Indonesian Sign Language (BISINDO). The fundamental difference between the two sign languages is that SIBI uses one hand while BISINDO uses two hands. However, the research only examines BISINDO because this sign language is more popular among deaf people. The deaf community of the Indonesian Movement for Deaf Welfare (GERKATIN) in Gowa Regency is the object of this study. The results of this study indicate that the influence of BISINDO news broadcasts on the understanding of the GERKATIN deaf community in Gowa Regency has a coefficient value of Y = 8.053 + 0.363 X. The constant number is 8.053 and the variable coefficient is 0.363, while the calculated t-value is 4.210, which is larger than the t-table of 1.674 with a significance level of 0.000 smaller than α = 0.05. Based on the statistical calculations obtained, the hypothesis in this study is that there is an influence between the two variables, which means that H0 is rejected and Ha is accepted. Meanwhile, the magnitude of the influence shows that the value of R is 0.501a and the coefficient of determination (Rsquare) obtained is 0.251 or 25.1%. This number indicates an influence of 25.1% on the variable and falls into the low category. The remaining 74.9% is influenced by other variables.